The Effects of the COVID-19 Pandemic on Pubertal Development in Girls: A Retrospective Evaluation of Girls Presenting with Precocious Puberty Before and During the Pandemic - Esin Karakılıç Özturan; Aslı Berru Arslan Özden; Tuğçe Kandemir; Şükran Poyrazoğlu; Firdevs Baş; Fatma Feyza Darendeliler (Çocuk Dergisi)
Objective: The timing of pubertal onset is a complex biological process influenced by various factors, many of which remain poorly understood. A notable increase in early puberty cases was observed during the COVID-19 pandemic. This study evaluated girls presenting with early or precocious puberty both during and in the five years before the pandemic. Methods: Thirty-six girls (Group 1) with suspected early puberty during the COVID-19 pandemic (March 2020–July 2021) and forty girls (Group 2) diagnosed with central precocious puberty between 2015 and 2019 were included. Retrospective data on demographic, anthropometric, clinical, and laboratory findings were analyzed. Results: The median (IQR) age at presentation was 8.07 (1.37) years in Group 1 and 7.89 (1.35) years in Group 2 (p=0.038). No significant differences were observed between the groups regarding height SDS, BMI-SDS, bone age, or Δ target height–predicted adult height SDS. Conclusions: Despite a common association between obesity and early puberty, no differences in BMI were identified in this cohort. Environmental factors related to the pandemic conditions may have influenced the timing of puberty. Larger studies with broader populations are needed for definitive conclusions.